Sweet success: How to Understand the Men in Your Business Life and Win with Your Own Rules - Stechert, Kathryn B. (New York Macmillan Publishing Company, 1986)
Sweet Success is the firts no-holds-barred analysis of how men and women differ on the job, and how you can use these differences to move to the top. Kathryn Stechert presents the most up-to-date research on gender studies and applies this new information to the workplace.
Keywords: Business English